Faith in Mount Fuji : the rise of independent religion in early modern Japan - Sawada, Janine Anderson, 1953- (University of Hawaiʻi Press, 2022)
Even a fleeting glimpse of Mount Fuji's snow-capped peak emerging from the clouds in the distance evokes the reverence it has commanded in Japan from ancient times. Long considered sacred, during the medieval era the mountain evolved from a venue for solitary ascetics into a well-regulated pilgrimage site. With the onset of the Tokugawa period, the nature of devotion to Mount Fuji underwent a dramatic change. Working people from nearby Edo (now Tokyo) began climbing the mountain in increasing numbers and worshipping its deity on their own terms, leading to a widespread network of devotional associations known as Fujikō.In Faith in Mount Fuji Janine Sawada asserts that the rise of the Fuji movement epitomizes a broad transformation in popular religion that took place in early modern Japan. Drawing on existing practices and values, artisans and merchants generated new forms of religious life outside the confines of the sectarian establishment. Sawada highlights the importance of independent thinking in these grassroots phenomena, making a compelling case that the new Fuji devotees carved out enclaves for subtle opposition to the status quo within the restrictive parameters of the Tokugawa order. The founding members effectively reinterpreted materials such as pilgrimage maps, talismans, and prayer formulae, laying the groundwork for the articulation of a set of remarkable teachings by Jikigyō Miroku (1671-1733), an oil peddler who became one of the group's leading ascetic practitioners. His writings fostered a vision of Mount Fuji as a compassionate parental deity who mandated a new world of economic justice and fairness in social and gender relations. The book concludes with a thought-provoking assessment of Jikigyō's suicide on the mountain as an act of commitment to world salvation that drew on established ascetic practice even as it conveyed political dissent.Faith in Mount Fuji is a pioneering work that contains a wealth of in-depth analysis and original interpretation. It will open up new avenues of discussion among students of Japanese religions and intellectual history, and supply rich food for thought to readers interested in global perspectives on issues of religion and society, ritual culture, new religions, and asceticism.